Are Phenacoccus solani Ferris and P. defectus Ferris (Hemiptera: Pseudococcidae) distinct species? - Chatzidimitriou, Evangelia; Simonato, Mauro; Watson, Gillian W.; Martinez-Sañudo, Isabel; Tanaka, Hirotaka; Zhao, Jing; Pellizzari, Giuseppina (Zootaxa, 2016)
Among the Nearctic species of Phenacoccus (Hemiptera: Pseudococcidae), Phenacoccus solani Ferris and P. defectus Ferris are morphologically similar and it can be difficult to separate them on the basis of microscopic morphological characters of the adult female alone. In order to resolve their identity, a canonical variates morphological analysis of 199 specimens from different geographical origins and host plants and a molecular analysis of the COI and 28S genes were performed. The morphological analysis supported synonymy of the two species, as although the type specimens of the "species" are widely separated from each other in the canonical variates plot, they are all part of a continuous range of variation. The molecular analysis showed that P. solani and P. defectus are grouped in the same clade. On the basis of the morphological and molecular analyses, P. defectus is synonymized under the senior name P. solani, syn. n.